HISTORY OF THE SAYID ATALYK MADRASAH (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the construction history, architectural features, and place of the Sayid Atalyk madrasah in Denau – one of the ancient cities of the Surkhandarya oasis – within the architecture of the Denau bekdom.